Low resistance but high resilience to drought of flushing Norway spruce seedlings. (2nd April 2021) - Hájíčková, Martina; Plichta, Roman; Urban, Josef; Volařík, Daniel; Gebauer, Roman
Abstract: Spring drought episodes are becoming more frequent and intensive in European temperate forests. To study tree resilience to spring drought, Norway spruce seedlings were exposed to three levels of drought stress (well-watered (W), moderately stressed (M) and severely stressed (S)) for 42 days and then fully irrigated for 14 days. Drought strongly reduced gas exchange parameters for both M and S seedlings. After 42 days, stomatal conductance was lower by 83 and 97% in M and S, respectively, than in W seedlings. Respiration prevailed over photosynthesis in S seedlings at the end of the drought period. Drought mostly reduced longitudinal growth, especially in shoots and needles. Xylem growth reduction was caused mainly by a lower number of newly produced tracheids, not by changes in their size. Norway spruce seedlings showed good resilience to spring drought, as the observed physiological parameters started to recover after rewatering and seedlings started to sprout and form new tracheids. In M seedlings, all physiological traits recovered to the level of W seedlings during the 14-day irrigation period but the recovery took longer in S seedlings. Shoots and needles did not regrow in length but leaf mass per area increased during the recovery phase. To conclude, Norway spruce seedlings showed good resilience to spring single-drought event, but time necessary to full recovery from stress could make seedlings more vulnerable to recurrent drought events.